The Influence of Atmosphere, Price and Facilities Provided on Consumer Satisfaction at Meraki Cafe, Cirebon City, West Java - Akhmad Jaeroni; Zikri Muhammad Rafli; Nova Rolani; Wahidi Wahidi (Return : Study of Management, Economic and Bussines, 2024)
Enjoying a banquet at a cafe has become a new habit or lifestyle trend for millennials today. Consumer satisfaction is always a must to nte paid attention to by every business person, especially the café sector in carrying out their business activities. The purpose of this study is to analyze how much the atmosphere, price and facilities affect consumer satisfaction at Meraki Cafe, both partially and simultaneously. The research method used was quantitative with a sample of 100 respondents with 20 indicators. After the data was collected, the researcher continued the analysis with a linear regression study using SPSS 24. The results and discussions obtained were that the atmosphere variable affected consumer satisfaction, the price affected consumer satisfaction, the facility affected consumer satisfaction, as well as when tested simultaneously the three variables had a significant effect. The impression obtained from this study is that Meraki café managers can pay attention to the three variables, namely atmosphere, price and facilities.